A New Arc-Disjoint-Trees scheme for survivable multicasting in mixed-graph sparse-splitting optical networks - Raposo, Luis (2016)
Abstract—This work addresses the problem of survivable multicast request provisioning in mixed-graph optical networks, where only a fraction of the nodes have optical splitting capabilities. An effective scheme for the calculation of a pair of disjoint trees, namely the New Arc-Disjoint Trees (NADT) protection scheme, is presented. The key idea of this technique is to gradually construct the primary tree, verifying that after the addition of each one of the destinations of the multicast session, a secondary (arc-disjoint) tree can still be obtained. The proposed protection technique is combined with two existing heuristics for multicast routing in mixed-graph sparse-splitting networks. Performance results demonstrate that the proposed NADT protection technique clearly outperforms the conventional approach in terms of blocking ratio, and presents a negligible increase of the average cost of the derived pair of arc-disjoint trees.